The Commitment of Social Workers in the UK: Committed to the Profession, the Organisation and Service Users?. Issue 3 (26th May 2016) - Collins, Stewart
Abstract : Commitment is defined and distinguished from associated concepts such as job satisfaction and motivation. Commitment in social work is important because it involves a deep attachment and bond to the profession and perhaps the organisations of social work and dedication to providing high-quality services to service users. There are clear benefits derived from commitment to social work for the social work profession, social work organisations and service users, associated with effort, focus, stability, consistency, productivity and high retention and low turnover rates. The commitment of social workers is explored through various career stages, ranging from experiences during qualifying education and training through the early years following qualification to work as a more experienced social worker. Commitment to service user groups is considered with a focus on child welfare. Several variables that affect commitment are explored, including experience, age, gender and the location and setting in which social work takes place. Suggestions are made for developing the commitment of social workers, based on research, including selection, mutual co-worker support, differential supervision, opportunities to influence organisational decision-making and education and training opportunities.